2010
DOI: 10.1002/pip.938
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of fine line printed and light‐induced plated contacts on silicon solar cells

Abstract: The properties of fine-line printed contacts on silicon solar cells, in combination with light-induced plating (LIP), arc presented. The seed layers are printed using an aerosol system and a new metallization ink called SISC developed at Fraunhofer ISE. The influence of multiple layer printing on the contact geometry is studied as well as the influence of the contact height on the line resistivity and on the contact resistance. The dependence between contact resistance and contact height is measured using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 11 publications
2
22
0
Order By: Relevance
“…The silver metal, glass layer formed by glass frit in the paste during co-firing process at Si surface, and a-SiNx:H film were removed by using 3 HNO and HF mixture solutions to delineate the footprints of the etched Ag crystallites into the Si surface [5].…”
Section: Methodsmentioning
confidence: 99%
“…The silver metal, glass layer formed by glass frit in the paste during co-firing process at Si surface, and a-SiNx:H film were removed by using 3 HNO and HF mixture solutions to delineate the footprints of the etched Ag crystallites into the Si surface [5].…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has shown that lines with a metallised area well below 100% can provide good solar cell properties after Ag‐LIP . For that reason, the most important response to take into account for the process optimisation is the line width followed by the line metallised area.…”
Section: Doe N°3: Fine Tuning and Confirmationmentioning
confidence: 99%
“…Rising silver prices affect the production costs because of the silver required for metallization: Solely the front side metallization accounts for about 20 % of standard cell production costs [1]. However, the front-side metallization is also vulnerable to many losses, including resistivity at the metal/semiconductor interface, line resistivity of fingers, and losses due to optical shading [2].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the ink components with regard to etching depth, contact formation and resulting silver layer is essential for the second metallization step by light-induced plating [2,5]. Curing temperature and duration have been varied to obtain best results [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation